1993
DOI: 10.1080/07315724.1993.10718356
|View full text |Cite
|
Sign up to set email alerts
|

Fatty acids in some common food items in Canada.

Abstract: Fat content and fatty acid (FA) composition of 100 common items in 17 food categories from the Canadian retail market were determined. Of these, 52 samples were made from partially hydrogenated fat. Their fat (in parentheses) and trans FA levels were as follows: breads (3.7% fat) 15.7%, hamburger buns (5.5% fat) 26.3%, cakes (8.7-36.7% fat) 10.1-25.7%, candies/chocolates (27.1% fat) 11.1%, cereals (1.3-12.9% fat) 9.2-33.7%, cookies (5.0-40.5% fat) 7.6-38.7%, crackers (9.2-33.0% fat) 13.8-35.4%, donuts (16.6-29… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
1
6

Year Published

1994
1994
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 27 publications
2
22
1
6
Order By: Relevance
“…The levels of trans fatty acids in all the sweet biscuits and crackers are relatively low by comparison with U.S. and Canadian products (Enig et al, 1983;Ratnayake et al, 1993). Both pastry and cakes have moderate levels of trans fatty acids in the fat.…”
Section: Discussionmentioning
confidence: 97%
“…The levels of trans fatty acids in all the sweet biscuits and crackers are relatively low by comparison with U.S. and Canadian products (Enig et al, 1983;Ratnayake et al, 1993). Both pastry and cakes have moderate levels of trans fatty acids in the fat.…”
Section: Discussionmentioning
confidence: 97%
“…In studies done in Australia and Canada high level of TFA was found in over 10% of food items analyzed and the authors also found great variability in TFA content in crackers, doughnuts and chocolate wafer biscuits. Earlier studies have also reported varied TFA level within similar food items due to type of oil used in preparation [9][10][11][12][13][14][15][16]. These variability reflects the difficulty in assessing TFA intake in a population especially by dietary methods which depend on food composition tables.…”
Section: Discussionmentioning
confidence: 99%
“…5 These foods are a major source of trans and saturated fatty acids; together, they account for over 50% of total fat intake in many samples. 24 One of the aims of the present study was to determine whether there was any difference in trans fatty acid intake between obese and control prepubertal children; no statistically significant difference was detected. It must be stressed that, in the present study, estimated dietary trans fatty acid intake in prepubertal Spanish children was lower (less than 1 g/day or 0.4% of total energy) than that reported for adults in other European countries (1.2-6.7 g/day in men and 1.7-4.1 g/day in women, accounting for 0.4-2.5% of total energy intake), 25 and in the United States (2.6% of total energy).…”
Section: Discussionmentioning
confidence: 99%